Evaluation of effectiveness of school-based nutrition education in improving the consumption of pulses-based food among female adolescents in Northwest Ethiopia: a cluster randomized controlled trial - Fantahun Ayenew Mekonnen; Gashaw Andargie Biks; Telake Azale; Netsanet Worku Mengistu (BMC, 2023)
Abstract Background Protein undernutrition is a prevalent health problem in Ethiopia severely affecting the reproductive outcome of women. This is mainly because of inadequate consumption of protein due to the high cost of animal-origin food and the lack of knowledge about the benefits and the methods of preparation of pulses-based foods. Therefore, this trial was conducted to evaluate the effectiveness of nutrition education in improving the consumption of pulses-based foods among female adolescents. Methods A two-arm pragmatic cluster randomized controlled trial was conducted among female adolescents in Northwest Ethiopia. Clusters were schools assigned into intervention and control groups by cluster randomization. The trial participants were female adolescents. The intervention was pulses-based nutrition education, and the comparator was the usual dietary practice of adolescent girls. The education was delivered over four weeks on a 45-60 min session per week basis. The primary outcome of the intervention was pulses-based food consumption, and the secondary outcomes were knowledge and attitude about pulses food. Data on the outcome and the confounding variables were collected at baseline and end-line of the intervention. The analysis was based on intention-to-treat analysis, and a log-binomial logistic regression model was fitted to the data to calculate relative risk with the corresponding p value adjusted for baseline characteristics. The intervention was considered effective when the p value was < 0.05. Results A total of 269 intervention and 278 control participants from the four clusters completed the trial making response rates of 92.1% and 95.2%, respectively. The pulses-based nutrition education enabled participants in the intervention group to maintain their pulses-based food consumption state, while participants in the control group significantly reduced their consumption by about threefold [ARR; 95% CI 2.99 (1.87, 4.79)] from harvesting to non-harvesting season. The consumption of pulses-based food was higher by 16% among the intervention participants as compared to the control participants [ARD; 95% CI 0.16 (0.10, 0.21)]. Conclusion Pulses-based nutrition education is effective in improving the consumption of pulses-based food among female adolescents. Therefore, policies and strategies are required to integrate this intervention in the school nutrition program. Trial registration: The trial was registered in the Pan African Clinical Trials Registry (PACTR202111813445259) on 02 November 2021.